(3JWHjbGJ HGSJNOGe (BSPSSs - (3UdGM GdOjf MSjf(B, (3GdgjJjs ((3YeGf(B:s (3OGQ hGFd ddWHGYI h GdfTQ(B,s, 2006)
(3jYGdL gPG GdcJGH(B:(3WHjYI heaghe GdEMUGA,JHhjH hYQV GdHjGfGJ,ebGjjS GdfRYI GdeQcRjI,ebGjjS GdJTJJ,fXQjI GdEMJeGdGJ,GdJhRjYGJ GdEMJeGdjI,GdeYGjfI GdEMUGFjI,ENJHGQ GdaQVjGJ,JWHjbGJ HESJNOGe HQfGeL(Bspss(3,GdEfMOGQ,GdCQbGe GdbjGSjI(B. s
(3HjHdjhZQGajG U(B.500 (3edGMb U(B. 501s
Keywords: (3GMUGA hUajs; (3GdEOGQI(B--(3CSGdjH EMUGFjIs; (3GdWQb GdEMUGFjIs; (3HQGeL GdMGShHs